Development of frozen french fries - Madulid, Angelita A.
A frozen French fried potato product developed using the Fina variety. The choice of the variety was based on the results of the objective tests which include determination of specific gravity and analyses of total solids, starch, reducing sugars and total sugars. The variables investigated in standardizing the procedure for frozen French fries were peeling and blanching treatments, length of frying, and method of freezing. For peeling, the optimum time of immersion at which the peels were scraped easily was 5 minutes in 10% lye and 4 minutes in 15% lye at 71°C. Employing the two-stage blanching method, the first stage of which was water blanching for 6 minutes at 71 - 73°C and the second stage blanching in 1% sodium acid pyrophosphate for 30 seconds at 82°C yielded French fries with desirable pale, golden brown color and with no off-flavor. Frying time of 5 minutes at 177° - 184°C was adequate to produce mealy internal texture. The use of a blast freezer at -40°C and a household freezer t -23° yielded frozen French fried which exhibited no significant difference in texture and which were preferred over the unfrozen French fries. A storage study using storage temperature of -23°C and 13°C was conducted. Results of the subjective tests indicated that storage at 13°C for 5 days already caused deterioration in favor and texture, whereas storage at -23°c for 27 days allowed the retention of desirable qualities of frozen French fries.